2016
DOI: 10.5897/err2016.2828
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among creative (Mis) fit, college culture, creative and academic self-efficacy

Abstract: Although person-environment fit (PEF) has been extensively studied in organizational psychology and business literature, its application to educational context has been limited. The current study used PEF framework in terms of creativity within the context of higher education. The nature of relationship between person-environment fit, college culture, creative and academic self-efficacy has been investigated. Analyses based on two different formulations of PEF indicated that college culture, creative and acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…High mean scores of personal and environmental dimensions and the fit between the two dimensions indicate high capacity or probability for creative expression and accomplishment. The Cronbach's alpha coefficients were .84-.87 and .83-.90 for personal and environmental dimension, respectively (Cayirdag, 2016;Sen et al, 2014). In the current study, the Cronbach's alpha coefficient was .88 and .87 for personal and environmental dimension.…”
Section: Measurementsmentioning
confidence: 95%
See 2 more Smart Citations
“…High mean scores of personal and environmental dimensions and the fit between the two dimensions indicate high capacity or probability for creative expression and accomplishment. The Cronbach's alpha coefficients were .84-.87 and .83-.90 for personal and environmental dimension, respectively (Cayirdag, 2016;Sen et al, 2014). In the current study, the Cronbach's alpha coefficient was .88 and .87 for personal and environmental dimension.…”
Section: Measurementsmentioning
confidence: 95%
“…Only Sen et al (2014) and Cayirdag (2016) applied PEFSC in the Turkish population and culture. Therefore, we aim to further examine the convergent, discriminant, and incremental validities of PEFSC in the current study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The former group examined the relationships between CSE and creativity (Broekhoven at al., 2020;Haase et al, 2018); CSE and creative performance (Chang & Jaisook, 2020;Lemons, 2010;Li & Wu, 2011;Paek et al, 2016;Park et al, 2021;Reiter-Palmon et al, 2012;Royston & Reiter-Palmon, 2019); CSE and creative thinking (Anderson & Graham, 2021;Kharkhurin, 2017 (Beghetto, 2009). At the same While examining the studies on personal characteristics, we found that Karwowski (2016) analyzed the changes occurred in 6 months (short-term) and 20 months (medium-term) periods in CSE and Review of the studies that examined the relationships between CSE and environmental factors revealed that studies investigated the effects of parents (Gralewski & Jankowska, 2020;Liang & Yuan, 2020), peers (Karwowski, 2015;Liu et al, 2016), and personenvironment fit (Cayirdag, 2016).…”
Section: Research Issues/themesmentioning
confidence: 71%
“…However, in typical studies on fit, this is seldom the case. Some research focuses on specific topics such as creativity (Nur, 2016) or demands resulting from technology-enhanced learning (Wang et al, 2020) but without investigating the relationship to broader assessments of perceived fit. Nevertheless, knowing which specific demands and abilities (e.g.…”
Section: Fit Between Demands and Abilitiesmentioning
confidence: 99%